2023
DOI: 10.1021/acsmaterialslett.2c00923
|View full text |Cite
|
Sign up to set email alerts
|

Surface Chemistry of Gold Nanoparticles for Bacterial Detection and Antimicrobial Applications

Abstract: Bacteria can infect the human body and cause disease, which endangers public safety. The emergence of multidrug-resistant bacteria poses a great challenge on the treatment of bacterial infections. Quickly detecting pathogenic bacteria and effectively killing them are of great significance for the targeted treatment of bacterial infections. On one hand, gold nanoparticles (Au NPs) are widely used for the rapid detection of bacteria, because of their surface plasmon resonance properties that allow for a visible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 120 publications
0
10
0
Order By: Relevance
“…Localized surface plasmon resonance (LSPR) enhances electric field on the surface of metallic particle, hence and the fluorescent properties of dye molecule in close proximity to it [1,2]. It is usually observed that fluorescence lifetime decreased, and fluorescence intensity might either enhanced or quenched [3,4]. Mechanisms of the interactions between LSPR and fluorephores is explained by by equation ( 1), ( 2), (3), (4) and in Fig.…”
Section: Introductionmentioning
confidence: 97%
“…Localized surface plasmon resonance (LSPR) enhances electric field on the surface of metallic particle, hence and the fluorescent properties of dye molecule in close proximity to it [1,2]. It is usually observed that fluorescence lifetime decreased, and fluorescence intensity might either enhanced or quenched [3,4]. Mechanisms of the interactions between LSPR and fluorephores is explained by by equation ( 1), ( 2), (3), (4) and in Fig.…”
Section: Introductionmentioning
confidence: 97%
“…Currently, the enzyme-linked immunosorbent assay (ELISA) for bacterial detection is fast and shows good specificity through the specific binding of antibody and antigen . However, the expensive materials, and usually the need to do the modification of the antibody, result in a more complicated operation procedure, which greatly limits its application. , For multiple bacterial detection, polymerase chain reaction (PCR) technology is commonly used in clinical practice to identify bacteria cultured in culture media . By PCR, the bacterial DNA in the culture media can be amplified, and then the bacterial species can be determined by analyzing the size and sequence of the amplification products .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the rapid advancements in nanotechnology have presented a promising avenue for combating MDR bacteria and modulating inflammation. [12][13][14][15][16][17][18] However, there has been a notable scarcity of successful nano-antibacterial drugs specifically designed to address these challenges, with limited mentions of their clinical application. Moreover, two key shortcomings have hindered the practical implementation of these nanoantibacterial drugs: 1) The extended circulation and metabolism challenges associated with nanomaterials have raised persistent safety concerns.…”
Section: Introductionmentioning
confidence: 99%